Lessons of history : the Holocaust and Soviet terror as borderline events - Karlsson, Klas-Göran 1955- (Academic Studies Press, 2024)
"Lessons of history are often referred to in public discourse, but seldom in scholarly discussions. This book wants to change this by introducing an innovative scholarly, analytical model of historical lessons, starting from the basic three-fold perspective that you simultaneously are history, share history, and make history. Not any history is useful for extracting or using lessons. Here, what are denoted as borderline historical events, demonstrating both time-specific and time-transcending qualities, are suggested as useful materials. Scholarly works on the Holocaust and Soviet terror, from Raul Hilberg's and Robert Conquest's classical works of the 1960s to more recent books by Jan Gross and Timothy Snyder, are analyzed to identify lessons of history, and their change during a full half-century"--